ESCORE DE AGITAÇÃO (EA) DE BEZERROS NELORE - BARBOSA, Taciara Aparecida Duarte; SOUZA, Andrea Roberto Duarte Lopes; OLIVEIRA, Pedro Henrique Pereira; VILELA, Reíssa Alves; SANTOS, Tânia Mara Baptista (ANAIS DO ENIC, 2024)
-